Molly saves the day : a summer story - Tripp, Valerie; Backes, Nick (Madison, Wis. : Pleasant Co., 1988)
Molly conquers her fear of swimming underwater when she and the other campers at Camp Gowonagin divide into two teams to play Color War.
Keywords: Camps; Fear; World War, 1939-1945 -- United States